Legal basis for public environmental expertisein the implementation ofthe right toa healthy environment (Journal of actual problems of jurisprudence, 2018)
In this article,the author examinesthe problem ofthe mechanism ofrealization of the rightsto a healthy environment. Andforeseeinganalysis of the implementationof public environmental reviewof the Republic ofKazakhstan.Publicenvironmentalexamination is carried outin order to preventnegative impactson the environment,organized and carried outon the initiative ofcitizens andcivil society organizations.As well as offeringsome of the waysthe decisionmechanism for the implementationof public environmental review.Key words: environment, public environmental assessment, environmental legislation.